ENTREPRENEURS FOR ACCOMMODATION STANDARDS TO ENABLE SUSTAINABLE LONG-STAY TOURISM IN NAKHON NAYOK PROVINCE - Siripooththilak, Varinnar; Sooyanun, Kawin (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This article aimed to (1) study the readiness of accommodation operators in Nakhon Nayok Province to meet the service standards for long-stay tourism, and (2) develop preparation guidelines to promote the sustainability of tourism. The research used a qualitative approach. Data were collected through in-depth interviews with 22 operators and stakeholders. To conduct the in-depth interviews, key informants were selected purposively. The research instruments used were semi-structured interviews and content analysis. The results of the research found that operators still lacked sufficient knowledge and understanding of long-term accommodation standards, especially in terms of hygiene, safety, and sustainability. Consequently, the research presented 12 areas of preparation, covering areas including (1) building hygiene and equipment in the building, (2) cleaning equipment to prevent the spread of germs, (3) protection for staff, (4) accommodation environment, (5) reception area, (6) guest rooms, (7) restaurant and cooking area, (8) other additional services, (9) personnel, (10) safety, (11) resource management, environment, and community relations, and (12) operator responsibility, pricing, and identification of various services to build confidence among tourists and sustainably improve service standards.